On the level structure of the spherical even-even nuclei 1o6Pd and 118Sn - Hattula, Jorma (1969)
The disintegration of 30 s 106g¹⁰⁶ᵍRh has been studied by means of Ge(Li) and NaI(T1) detectors and detector combinations. A total of 93 gamma-rays have been assigned to this decay. The integral-bias summing coincidence spectrometer has been used in directional correlation measurements and the E2/M1 mixing ratio of the 616,0 keV 2₂⁺ - 2₁⁺ transition was measured direct. The levels of ¹⁰⁶Pd are compared with those predicted by the quadrupole vibrational model, and with levels from resonance neutron-capture, proton and deuteron inelastic scattering studies. Gamma rays in the disintegration of 5.0 s (1⁺), 8.5 s (7⁻, 8⁻) and 4.4 min (4⁺, 5⁺) ¹¹⁸In isomers and of 3.5 min (1⁺) and 5.1 h (8⁻) ¹¹⁸Sb isomers have been investigated using Ge(Li) detectors and Ge(Li) - NaI(T1) coincidence spectrometers. The decay schemes of these isomers have been constructed incorporating 17 levels in the product nucleus ¹¹⁸Sn, at the following energies (in keV): 0 (0⁺), 1229.5 (2⁺), 1757.5 (0⁺), 2043.1 (2⁺), 2056.4 (0⁺), 2280.3 (4⁺), 2321.3 (5⁻), 2326.4 (1⁺, 2⁺), 2402.7 (4⁺), 2488.8 (3⁺, 4⁺), 2496.5 (0⁺), 2575.2 (7⁻), 2677.3, 2733.7 (2⁺), 2929.8, 2963,5 (4⁺) and 3137.1 (0⁺). The structure of ¹¹⁸Sn is briefly discussed in view of results from recent quasiparticle-model calculations.